A legal good under art. 62 sec. 1 of the Act on Counteracting Drug Addiction of 2005 (Ius Novum, 2023)
The subject of this article’s interest is the regulation of Art. 62 sec. 1 of the Act on CounteractingDrug Addiction of July 29, 2005, often called in the literature as consumer possession. Thebasic problem related to the subject matter indicated in the title is related to the definitionof the legal interest in Art. 62 sec. 1 of the act. Contrary to appearances, its indication is nota simple or unequivocal matter, as there may be doubts as to whether such a good protectedby law exists and, if so, whether it should be protected under criminal law. The article alsoindicates the correlation of this legal good and the need to protect it with other legal goodsprotected by the Constitution (e.g., individual freedom). Finally, the article also defines thesignificance of the consent of the possessor of a given good for the exclusion of unlawfulnessor the absence of any attack on the legal good. Behavior taken with the consent of the owner,allegedly “violating” the legal interest, is after all an act that is consistent with the norm fromthe very beginning, and therefore there is no element of unlawfulness in it. As such, it is nota criminal act. There can be doubts whether in the case of possession and use of drugs, thereis a threat to the legal good, or whether it is a behavior that from the very beginning, due tothe consumer’s consent, is legal behavior. The article is critical of the existing criminal lawregulations, and its clue is the thesis about the exclusively medical and social, not criminallaw, problem of drug addiction.
Keywords: legal good; drug possession; criminal law; constitution